(untitled) (Research, Society and Development, 2021)
The species of the Lamiaceae family produce essential oils in the glandular trichomes, leaf surfaces, and in inflorescences, and can also produce many secondary compounds, which indicates great potential for study. The aim of this paper was to describe the chemical composition and the biological, antioxidant, antimicrobial, and antitumor activities of the essential oil of Cantinoa althaeifolia for the first time. The essential oil was obtained from the leaves by hydrodistillation and analyzed by gas chromatography mass spectrometry (GC/MS). The antioxidant activity was established by the phosphomolybdenum method. The minimum inhibitory concentration against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, and Candida albicans was determined. The lethality test of Artemia salina was performed. The cytotoxicity against murine fibroblasts (3T3), non-tumor cells (McCoy), murine melanoma (B16F10), and human breast carcinoma (MCF-7) cells was assessed. Five major compounds were isolated: himachalene (11.62%), spathulenol (10.08%), caryophylline oxide (9.93%), (E)-caryophylene (9.21%), and pogostol (6.31%). The phosphomolybdenum complex method showed positive results. The minimum inhibitory concentration was greater than 1000 μg/mL for the tested microorganisms. The mortality rate of Artemia salina was low. The tested cancer cell lines showed an IC50 of 12.5 and 25 μg/mL. These findings indicate that the essential oil of Cantinoa althaeifolia has antioxidant, antimicrobial, and antitumor activities.